Soil quality analysis in riparian areas for soil and water resource management - Iori, Piero; Da Silva, Reginaldo Barboza [UNESP]; Dias Junior, Moacir De Souza; Nakamura, Ricardo [UNESP]; Ferreira De Almeida, Luis Carlos [UNESP] (Taylor & Francis Ltd, 2019)
Cultivating areas adjoining watercourses can cause serious changes in the soil attributes, promoting negative environmental processes. The aim of this study was to assess the changes in the properties of soil and use comparative diagrams to compare soil quality in response to land use in riparian areas in Brazil. Based on the obtained data, a soil quality index was calculated for each type of land use, and comparative diagrams were drawn and compared to assess soil quality. Agricultural land use alongside rivers (riparian areas) has caused negative changes to the main properties of soil. Comparing diagram areas, land under banana cultivation, degraded pastures and silvopastoral land had values that were 40%, 36% and 29%, respectively, of diagram areas for the native forest. While banana cultivation caused the greatest negative changes to the physical and mechanical properties, silvopastoral land and degraded pastures caused the greatest negative changes to the chemical properties. The polygons formed, which were used to compare the reference areas to the areas for the three different agricultural land uses, differed in shape and area compared to reference values, proving that these comparative diagrams are a useful tool in the assessment of soil quality in riparian areas.
Keywords: Comparative diagrams; environmental impact; land adjoining watercourses; soil degradation